Life cycle inventory data development for greenhouse gas emissions of Thailand's electricity grid generation systems - Viganda Varabuntoonvit (2018)
LCA (Life Cycle Assessment) is a well known methodology to assess the impact on the environment over the life cycle of a product, process, or activity. This methodology is based on the LCI (Life Cycle Inventory) database, a data set of all resources (material and energy) that are consumed or emitted in order to produce 1 unit of the product. Because electricity is a basic infrastructure, a Thailand electricity grid LCI database is needed to assess the environmental impact not only for the product used in Thailand, but also for any product that is exported to other countries. A complete LCI database for the electricity grid in Thailand is not yet available, and the LCI database developed in this work applies from the fuel acquisition stage to the production stage. The analysis shows the unique characteristics of the Thailand electricity grid. An LCI database for each type of fuel and for each electricity generation system was developed. The characteristics of each type of fuel and electricity generation system are indicated in terms of Life Cycle GHG (Greenhouse Gas) emissions to reflect their global warming potential. Data on the Life Cycle GHG emission per kWh of electricity produced are also provided. The first Thailand LCI database for the fuels used in the electricity generation system was developed using data obtained from the EGAT (Electricity Generating Authority of Thailand), IPPs (Independent Power Producers), and PTT (Petroleum Authority of Thailand) during the Thai fiscal year 2005 (from October 2004 to September 2005). The database was used to analyze the current situation and the characteristics of the electricity generation system in Thailand and to compare it with the systems used in other developed countries. © 2008 The Berkeley Electronic Press. All rights reserved.